2020
DOI: 10.1038/s42005-020-00413-2
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of nonlinear electron-phonon coupling and vertex corrections in the Holstein model

Abstract: Determining the range of validity of Migdal's approximation for electron-phonon (e-ph) coupled systems is a long-standing problem. Many attempts to answer this question employ the Holstein Hamiltonian, where the electron density couples linearly to local lattice displacements. When these displacements are large, however, nonlinear corrections to the interaction must also be included, which can significantly alter the physical picture obtained from this model. Using determinant quantum Monte Carlo and the self-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…This comparison can be improved somewhat with 'renormalized ME' theory in which the phonon propagator is dressed by electron-hole bubbles [34]. Recently, there has been renewed interest in examining the limits of ME theory and when it breaks down [35][36][37][38][39]. Indeed, it has been shown that ME can work well for ω 0 << E F provided the electron phonon coupling is not too large, enabling estimates of T SC to be made by extrapolating DQMC results down to lower temperatures using ME calculations [35].…”
Section: Introductionmentioning
confidence: 99%
“…This comparison can be improved somewhat with 'renormalized ME' theory in which the phonon propagator is dressed by electron-hole bubbles [34]. Recently, there has been renewed interest in examining the limits of ME theory and when it breaks down [35][36][37][38][39]. Indeed, it has been shown that ME can work well for ω 0 << E F provided the electron phonon coupling is not too large, enabling estimates of T SC to be made by extrapolating DQMC results down to lower temperatures using ME calculations [35].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the harmonic description of phononic excitations in the medium provided by the Holstein model may not be sufficient, and the effects of anharmonic terms on the phases of Holstein systems should be taken into account. [32][33][34][35][36][37][39][40][41] Several approaches to include anharmonic effects have been considered, for example nonlinear coupling terms between fermions and phonons, [32][33][34][35][36][37] or quartic [38][39][40] or Gaussian 41 contributions to the phonon potential energy. Anharmonicity has also been considered in the context of Migdal-Eliashberg theory.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the superconducting state in such studies are found only by extrapolation from normal state properties, and, in addition, the QMC calculations are performed on relatively small lattices due to the huge complexity of the problem. The most commonly studied system in these works is the 2D Holstein model [8,[11][12][13][14][15][16], often with additional constraints such as half-filling, while 3D systems are rarely considered in numerical calculations, presumably due to the large computational complexity.…”
Section: Introductionmentioning
confidence: 99%